THE EFFECTS OF TEACHING MODEL AND VOCABULARY MASTERY TOWARDS STUDENTS WRITING ACHIEVEMENT - Atri Apriyani; Muhammad Sulhan (Universitas Indraprasta PGRI, 2021)
Abstract: This study was to know the teaching model and vocabulary mastery by students at state vocational high schools in Tangerang Regency when writing. The research methodology used is the experimental method. The population in this research was all of the 10th-grade students, with 680 students. The research findings are: 1) There is a significant effect of teaching model towards students writing achievement at State Vocational High School in Tangerang Regency. That is proved by sig value = 0.000 < 0.05 and Faccount = 29.298. 2) There is a significant effect of vocabulary mastery towards students writing achievement at State Vocational High School Tangerang Regency. That is proved by sig value = 0.000 < 0.05 and Faccount = 17.945. 3) There are no significant interactive effects of teaching model and vocabulary mastery towards students writing achievement at State Vocational High School Tangerang Regency. That is proved by sig value = 0.041 < 0.05 and Faccount = 4.486.Keywords: Teaching model; vocabulary mastery; writing achievement.